Mutations in the PH Domain of DNM1 are associated with a nonepileptic phenotype characterized by developmental delay and neurobehavioral abnormalities. Issue 2 (4th February 2018) - Brereton, Emily; Fassi, Emily; Araujo, Gabriel C.; Dodd, Jonathan; Telegrafi, Aida; Pathak, Sheel J.; Shinawi, Marwan
Abstract: Background: Dynamin 1 is a protein involved in the synaptic vesicle cycle, which facilitates the exocytosis of neurotransmitters necessary for normal signaling and development in the central nervous system. Pathogenic variants in DNM1 have been implicated in global developmental delay (DD), severe intellectual disability (ID), and notably, epileptic encephalopathy. All previously reported DNM1 pathogenic variants causing this severe phenotype occur in the GTPase and Middle domains of the dynamin 1 protein. Methods: We used whole‐exome sequencing to characterize the molecular basis of DD and autistic symptoms in two identical siblings. Results: The twin siblings exhibit mild to moderate ID and autistic symptoms but no epileptic encephalopathy. Exome sequencing revealed a genetic variant, c.1603A>G (p.Lys535Glu), in the PH domain of dynamin 1. Previous in vitro studies showed that mutations at Lys535 inhibit endocytosis and impair PH loop binding to PIP2. Conclusions: Our data suggest a previously undescribed milder phenotype associated with a missense genetic variant in the PH domain of dynamin 1. Abstract : We describe two identical twin siblings with a genetic variant in the PH domain of dynamin 1 associated with mild to moderate ID and autistic symptoms but no epileptic encephalopathy. Previous in vitro studies support the pathogenicity of mutations at Lys535. Our data support a novel and milder phenotype associated with PH domain variants of dynamin 1.